Cold CO2 injection for balancing interfacial tension decrease and viscosity increase - Hamdi, Z. (Society of Petroleum Engineers, 2016)
CO2 injection has been used for decades in the petroleum industry as a successful tertiary recovery method. The main impact of CO2 on the reservoir is interfacial tension (IFT) reduction between the crude oil and CO2 which leads to better sweep. Decrease in the temperature can cause lower IFT between CO2 and hydrocarbons. Yet, lowering the temperature will cause an increase in oil viscosity which negatively affects the oil recovery. In this study, we have calculated the change in IFT and viscosities of crude oil and CO2to examine if a low IFT optimum point does exist where a low viscosity ratio between the two fluids is observed. To obtain IFT between CO2 and crude oil, the Parachor model is used. Viscosities of the fluids are calculated using a commercial simulator. Then, simulations of CO2 injection is conducted as a tertiary recovery method to calculate the overall recovery as well as investigating the existence of the optimum point. The results show that based on the composition of the crude oil, there is an optimum temperature beyond which the IFT would not decrease as well as the viscosities are at the optimum point suitable for recovery. Therefore, it is concluded that IFT has a more important role in the ultimate recovery than the viscosity of the fluids. Â© 2016 Society of Petroleum Engineers. All rights reserved.